Investigation of Mechanical and Durability Properties of Concrete Mixed with Water Exposed to a Magnetic Field. (12th October 2021) - Dharmaraj, R.; Arunvivek, G. K.; Karthick, Alagar; Mohanavel, V.; Perumal, Bhagavathi; Rajkumar, S.
Abstract : Water is a crucial element in the concrete mix and is alone responsible for concrete work ability and cement hydration. The massive quantity of potable water consumed during the production of concrete is a concern. In general, fresh and hard concrete qualities are most influenced by the quantity and water quality. The use of magnetic water in concrete gives many benefits when it comes to increasing its properties. A substantial quantity of water can be saved by substituting potable water with magnetized water in concrete. In this study, the effects of magnetized water on the concrete's mechanical and durability properties were tested. Four different combinations were made using potable water and magnetic water. Mechanical properties including compression, flexural, tensile strength, and SEM analysis were evaluated. Water absorption, acid resistance, and corrosion resistance were all tested as part of the durability tests. According to the results of the experiments, employing magnetic water for concrete preparation and curing enhanced the mechanical properties and durability. Concrete mix MMMC prepared and subjected to curing using magnetized water has a 14.86% greater compressive strength than ordinary concrete. Similarly, tensile and flexural strength of mix MMMC amplified to 14.32% and 14.02%, respectively. Besides, the consumption of chemical admixtures also considerably reduced in magnetized water imbibed concrete.